Comparative transcriptomic analyses of thymocytes using 10x Genomics and Parse scRNA-seq technologies - Igor Filippov; Chinna Susan Philip; Leif Schauser; Pärt Peterson (BMC Genomics)
Abstract Background Single-cell RNA sequencing experiments commonly use 10x Genomics (10x) kits due to their high-throughput capacity and standardized protocols. Recently, Parse Biosciences (Parse) introduced an alternative technology that uses multiple in-situ barcoding rounds within standard 96-well plates. Parse enables the analysis of more cells from multiple samples in a single run without the need for additional reagents or specialized microfluidics equipment. To evaluate the performance of both platforms, we conducted a benchmark study using biological and technical replicates of mouse thymus as a complex immune tissue. Results We found that Parse detected nearly twice the number of genes compared to 10x, with each platform detecting a distinct set of genes. The comparison of multiplexed samples generated from 10x and Parse techniques showed 10x data to have lower technical variability and more precise annotation of biological states in the thymus compared to Parse. Conclusion Our results provide a comprehensive comparison of the suitability of both single-cell platforms for immunological studies.